2019
DOI: 10.2147/idr.s202346
|View full text |Cite
|
Sign up to set email alerts
|

<p>Simvastatin improves the eradication rate of <em>Helicobacter pylori</em>: upper Egypt experience</p>

Abstract: Background: Helicobacter pylori infection is one of the most prevalent chronic bacterial human infections worldwide. Helicobacter pylori colonizes the gastric mucosa and causes persistent gastritis that may progress to gastric cancer. Increased resistance of H. pylori presents a major problem in most countries. Statins, including simvastatin, which are currently used to treat hypercholesterolemia, appear to have potential synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
3
13
1
Order By: Relevance
“…Only in the standard triple therapy was the use of these drugs associated with lower effectiveness. This finding is opposed to what was described in the randomized studies of Nseir and Hassan, in which the addition of simvastatin 20 mg twice daily to the standard triple therapy containing clarithromycin and amoxicillin showed a statistically significant increase in effectiveness of 15–20% [ 26 , 35 ]. Despite their findings, several voices questioned whether this hypothetical increase would be clinically significant considering the unacceptable effectiveness rate reported for the standard triple therapy over the years in most geographical areas [ 1 , 6 , 36 ].…”
Section: Discussioncontrasting
confidence: 79%
“…Only in the standard triple therapy was the use of these drugs associated with lower effectiveness. This finding is opposed to what was described in the randomized studies of Nseir and Hassan, in which the addition of simvastatin 20 mg twice daily to the standard triple therapy containing clarithromycin and amoxicillin showed a statistically significant increase in effectiveness of 15–20% [ 26 , 35 ]. Despite their findings, several voices questioned whether this hypothetical increase would be clinically significant considering the unacceptable effectiveness rate reported for the standard triple therapy over the years in most geographical areas [ 1 , 6 , 36 ].…”
Section: Discussioncontrasting
confidence: 79%
“…The test showed insignificant mean difference in both the groups at baseline and after 14 days and the p-value was also found to be insignificant between both the groups (0.741). A former study conducted by Hassan et al, 2019 also showed no significant change between the two groups before and after treatment [20]. similar results was also showed by [21].…”
Section: Discussionsupporting
confidence: 69%
“…Also, depletion of cholesterol has been demonstrated to attenuate CagA-induced pathogenesis [ 59 ]. Adding statin to the standard triple therapy may improve the eradication rate of HP infection [ 60 ].…”
Section: Discussionmentioning
confidence: 99%